Bullying And Its Relationship To Anxiety, Depression, And Self-Esteem - Madepan Mulia; Rosmiati Rosmiati; Rezqiqah Aulia Rahmat; Rahmat Pannyiwi; Lumastari Ajeng Wijayanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Bullying is a mental health problem commonly experienced by adolescents and can have serious psychological impacts on victims. The effects of bullying include anxiety, depression, and decreased self-esteem. This study aims to determine the relationship between bullying and levels of anxiety, depression, and self-esteem in adolescents. This study used quantitative methods with an analytical design and a cross-sectional approach. Sectional. The research sample was students at educational institution X. Data were collected using a questionnaire on bullying, anxiety, depression, and self-esteem, then analyzed using the Chi- Square test. The results showed a significant relationship between bullying and anxiety, depression, and self-esteem (p < 0.05). The conclusion of this study is that bullying is closely related to mental health disorders in adolescents.